A inserção do surf nos Jogos Olímpicos de verão Tóquio 2020: as estratégias dos agentes e instituições no campo esportivo - Stachevski, Thiago Weigert (2020)
The Olympic Games represent the biggest sporting event in the world and is capable of gathering athletes from more than 200 National Olympic Committees (NOC) to compete in approximately 28 sports. In each Olympic cycle some sports could be included or removed from the honourable Olympic Games field. In 2020, the new sports will be baseball/softball, karate, sport climbing, skateboarding and surfing. The last three are examples of extreme sports, a category that was only included in the Olympic Games of Beijing 2008 on a minor scale and with the inclusion of BMX. The related strategies of this innovation are the focus of this study, more specifically the inclusion of surfing in the Olympic Games. This present study has a qualitative nature, based on document analysis, in which sport news and journalism reports about the subject on the following databases: BBC, COI, Folha de São Paulo, Forbes, Front Office Sports, Globo Esporte, Globoesporte.com, HardCore, ISA, Olympic Channel, Reuters, Super Interessante, Surfer, SurferToday, Surf Total, Terra, The Inertia, The Nation, The Telegraph, Tokyo 2020, Veja e WSL, were analysed with the main objective of having a better understanding about which agents and institutions and their respective strategies on making this decision. The data was analysed based on the features of speech analysis, looking for the implicit information, and also based on the Field Theory of Pierre Bourdieu. In conclusion, the main institutions: The International Olympic Committee, Japanese Olympic Committee, International Surfing Association and World Surf League, along with their respective agents within the sports field, in their dispute for the accumulation of capitals, have developed unique strategies to include surfing in the Tokyo 2020 Olympic Games. In general, the COI’s strategies and ISA’s strategies converge in order to include surf at the Olympic Games. Their fights for social capital, symbolic capital and, more importantly, economic capital, have led the strategies to focus on the prestige that a privileged position within the field could offer, both in terms of material and symbolic gains, as well as social distinction.